MENINGKATKAN KESADARAN MASYARAKAT TENTANG KEBERSIHAN DAN KEINDAHAN LINGKUNGAN MELALUI KEGIATAN GOTONG ROYONG DAN PENGHIJAUAN DI DESA TANDEM HILIR II - K. Afni; N.K. Ilmi; Mardiati Mardiati; I. Wirevenska; N. Yultisa (Universitas Islam Sumatear Utara, 2023)
This community service activity aims to increase public awareness and concern for the cleanliness and beauty of the environment around the community in Dusun IX, Desa Tandem Hilir II. The method used in this activity is the socialization method regarding the importance of cleanliness and the beauty of the surrounding environment and inviting the community to take part in the Mutual Cooperation and Greening activities that we are currently carrying out. Based on the results of the activity, it can be concluded that this activity can be said to be successful and the community around Dusun IX Desa Tandem Hilir II, is very enthusiastic in participating in the Mutual Cooperation and Greening activities which are hoped that later the community will care more about the cleanliness and beauty of the environment.